Prospects of tourism in Malaysia: A situational study focusing on socio-cultural and environmental aspects - Karim, A. H. M. Zehadul; Md. Noon, Hazizan; Mohd Noor, Noor Azlan; Makol-Abdul, Pute Rahimah (Sustainable Tourism Research Cluster Universiti Sains Malaysia, 2013)
Malaysia is perhaps one of the most unique countries of the world, being strategically situated on the gate-way location of global routes with a wonderful eco-environmental setting. Being a pluralistic society, it inherits its own traditional culture with harmonious integration of the diverse ethnic groups living in a very peaceful and politically stable situation. With all its economic potentials, Malaysia has recently emerged as a newly-developed nation with a huge infrastructural growth in its industrial and manufacturing sectors. Due to these developments and other eloquent features, people from abroad become largely attracted to this land and thus, they frequently arrive here as visitors and tourists. As recently as in the year 2005, it is reported that at least 16.7 million international tourists from outside visited Malaysia bringing about 30 billion ringgit in terms of foreign currency in this country (see Badruddin et.al. 2007). At present, tourism may be regarded as the largest service-oriented industry in Malaysia contributing a great economic share in the national GDP and provides employment to a bulk of the population in the country. It brings civic pride and social prestige for Malaysia by making a kind of international linkages in global context. It takes Malaysian culture abroad and people from outside can get the touch of the unique Muslim heritage in Malaysian context. Based on this positive assumption, this proposed research will generate information in regard to knowing about the present situation of tourism in Malaysian context. Side by side, it is also recognized that tourism often damages eco-environments of a particular region of the country, which are over-used by the tourists. The natural habitats are dislocated, and also there occurs enormous social impacts on local values and community culture. From that perspective the paper is designed to deal with the issue of tourism in Malaysia from both positive and negative perspectives; and thus it will generate a discourse to conceptualize a rational framework for Malaysian tourism.